Growth Performance and Carcass Yield of Broiler Finishers Fed Diets Having Partially or Wholly Withdrawn Fish Meal - Yisa, A.G.; Edache, J.A.; Udokainyang, A.D.; Iloama, C.N. (International Journal of Poultry Science, 2013)
A four-week study was conducted to investigate the effect of partially or completely withdrawing fish meal from broiler finisher diets on growth performance and carcass yield. In a completely randomized design, ninety six (96) four-week-old Marshall Breed of broilers were allotted to four dietary treatments having 0, 50, 75 and 100% of their fishmeal content withdrawn. Each dietary treatment had 24 birds with 3 replicates of 8 birds. Results show that initial weights, final weights, average daily feed intake, average daily weight gain, feed conversion ratio and feed cost per kilogram gain were not negatively affected (P>0.05) by levels of fish meal withdrawal. Dressing percentages were also not significantly different (P>0.05) between treatment means. However, the percent carcass cut-up parts of breast, wings, thighs and drumsticks to live weight of birds fed diets with fish meal totally withdrawn were significantly less (P<0.05) than those of birds fed diets containing fish meal. From this study, it can be concluded that withdrawing fish meal from broiler finisher diets may not have any adverse effect on their growth performance provided protein is obtained from non-animal sources. However, total withdrawal of fish meal negatively affects optimum development of the cut-up parts and as such 0.5-1% fish meal may be included in broiler finisher diets for full development of carcass components.